Unruly Waters, Unsanitary Bodies Abject Terrains, Rehabilitation, and Infrastructures of Dispossession on the U.S.–Mexico Border - Carlos Martinez (Medicine Anthropology Theory, 2023)
Drawing on ethnographic fieldwork among homeless deportees living in the Tijuana River canal, I examine how the ‘rehabilitation’ of toxic terrains can have corporeal and social consequences for those inhabiting such spaces. For decades, the Tijuana River basin traversing the U.S.–Mexico border has been perceived by officials from both countries as an unruly body of water. Prone to persistent flooding, the canal also experiences flows of toxic sewage from Tijuana’s maquiladora industry. In recent years, the riverbed in Tijuana has been inhabited by homeless and drug using communities, many of whom have been deported from the U.S. In response, rehabilitation of the canal and forced drug rehabilitation have been conjoined and promoted by the state as solutions for managing this unruly terrain and its residents. I take the deployment of the term ‘rehabilitation’ targeting both homeless deportees and the canal as an opportunity to consider how the concurrent disciplining of landscapes and human populations has been a central and evolving feature of the Anthropocene. I examine how my homeless interlocutors have experienced ‘rehabilitation’ as a violent process of abjection, dispossession, and captivity, which has converted this transborder landscape structure into a carceral zone under the guise of urban sanitation and health promotion.